Parate Executie Clause in Mortgage Bond Versus Post-Default Authority to Sell ‒ Business Partners Limited v Mahamba (4568/2016) [2019] ZAECGHC 17 (26 February 2019) - Reghard Brits (Obiter, 2020)
The purpose of this note is to consider a case that came before a full bench of the Eastern Cape Division of the High Court in Grahamstown – namely, Business Partners Limited v Mahamba ((4568/2016) [2019] ZAECGHC 17 (26 February 2019)). The case touched on the age-old debate surrounding the validity of parate executie (summary execution or private sale) clauses in agreements that hypothecate property as security for the payment of a debt. Even though such clauses are popular in pledge agreements pertaining to movable property (including the hypothecation of incorporeal movables via a cession in securitatem debiti), this case involved a mortgage bond pertaining to immovable property. Moreover, as explained below, the impugned clause in casu technically was not a parate executie clause but an agreement entered into after the debtor defaulted on a loan.A parate executie clause generally seeks to entitle the secured creditor to dispose of the hypothecated property through a private sale – that is, without going through the normal court processes – when the debtor defaults on payment obligations under the loan agreement. The validity of parate executie clauses has been debated since at least Roman-Dutch times, while the debate has also featured in modern South African case law and literature. More recently a constitutional dimension has been added to (and has revived) the controversy by virtue of the right of access to courts guaranteed in section 34 of the Constitution of the Republic of South Africa, 1996 (the Constitution). There is also a significant difference depending on whether a pledge of movable or a mortgage of immovable property is involved. It is moreover necessary to distinguish between parate executie clauses included in the bond itself and agreements subsequent to a debtor’s default in terms of which a debtor authorised a creditor to sell the property without having to go through the court processes.In view of the judgment in Business Partners v Mahamba (supra), it is arguably necessary to revisit the matter and to clarify some aspects surrounding parate executie clauses, such as the circumstances under which they are valid and invalid as well as how they differ from similar contractual arrangements between debtors and creditors. It is also necessary to affirm the difference in this regard between pledges of movable and mortgages of immovable property. The case note also comments on the implications, in the residential mortgage foreclosure context, of the difference between parate executie clauses in mortgage agreements, on the one hand, and post-default agreements allowing a creditor to sell the property privately, on the other.